Morphological and Molecular Variability of Alternaria solani and Phytophthora infestans Causing Tomato Blights - Mugao, Lydia (International Journal of Microbiology, 2023)
Alternaria solani and Phytophthora infestans cause early and late blight diseases in tomato and potato, respectively. A. solani can survive for more than a decade in the soil, seed, or in plant residues at optimum temperature. The pathogen exhibits high molecular and genetic variation between isolates from potato and tomato plants, in different countries. Morphological studies reveal separate conidia borne singly on simple conidiophores. Spores are elongated, muriform, beaked, septate, and dark coloured. The mycelia are branched and septate. A. solani demonstrated a high genetic variability among isolates originating from the United States, Greece, Cuba, Canada, Russia, Turkey, South Africa, Brazil, and China based on vegetative compatibility groups and molecular markers (random amplified polymorphic DNA markers, random amplified microsatellite markers, and amplified fragment length polymorphisms). Different morphological and molecular variations indicate the presence of variability among the isolates. On the other hand, P. infestans is a diploid, obligate, heterothallic, and biotrophic oomycete, whose asexual lifecycle is characterized by alternating phases of sporangia germination, hyphal growth, and sporulation. The mycelia of P. infestans is coenocytic, multinucleate, and aseptate although the cross walls do not form in old cultures. Sporangia are borne singly on the branch tips of the alternately branched sporangiophore. Sporangium is hyaline and lemon shaped with a papilla at the distal end. Mating types A1 and A2 with different clonal lineages have been discovered in various parts of the world indicating variation in the species.